New papr reduction in ofdm systems by hybrid algorithm of pts and appr methods - Pradabpet, C.; Yoshizawa, S.; Miyanaga, Y.; Dejhan, K. (My University, 2009)
In this paper, we propose a new peak to average power ratio (PAPR) reduction technique by a hybrid algorithm based on a partial transmit sequence (PTS) and adaptive peak power reduction (APPR) methods. This technique is used in a system based on orthogonal frequency division multiplexing (OFDM OFDM has orthogonally modulated sub-carriers which unexpectedly give large PAPR and tends to reduce the power efficiency of a RF amplifier. To reduce PAPR, the sequence of input data is rearranged by PTS for the reduction of PAPR and then fed to APPR process in the proposed system. The APPR method controls the peak level of the modulation signal by an adaptive algorithm. It reduces modulation signals over a predefined range. A proposed reduction method consists of these two methods and realizes both advantages at the same time. In simulation results, the proposed method shows the improvement on PAPR, PSD, and also the high performance on bit error rate of an OFDM system.
Keywords: Adaptive peak power reduction (appr); Nonlinear hpa; OFDM; PAPR; PTS